Development Of A Telecommunications Regulatory Evaluation Model Based On The Five-Generation Framework By The International Telecommunication Union (Itu) - Gunawan, Arief Hamdani; Handayani, I Gusti Ayu Ketut Rachmi; Karjoko, Lego (UI Scholars Hub, 2024)
With the evolution of technology and changes in societal needs, regulations in the telecommunications industry should be adaptable in order to maintain accessibility, affordability, and quality of service standards. The ITU has developed an extensive assessment model for regulations that consists of five generations. This model evaluates telecommunication regulatory policies’ effectiveness and efficiency under fast evolving technological circumstances. Each generation will be broken down according to such indicators established by the ITU as policy effectiveness, adaptability to technological change, and impact on users of telecoms services. Through various regulatory stages this evaluation model brings out comprehensive understanding about achievements made as well as challenges faced during these periods that supports sustainable digital transformation.